Evaluation of Corneal Endothelial Cells and Morphology in Mitomycin-C Augmented Trabeculectomy - Shalini Dhiman; Ankur Kumar; Kishor Kumar (Delhi Journal of Ophthalmology)
Purpose: To evaluate the effect of Mitomycin-C (MMC) on corneal endothelial cells and morphology in Mitomycin-C augmented trabeculectomy Methods: In this study, 40 eyes of patients underwent trabeculectomy with Mitomycin-C (group 1) and 40 eyes of patients underwent trabeculectomy without Mitomycin-C (group 2). Specular microscopy was performed at 1 month and 3 month postoperatively. Outcome variables included corneal endothelial cell density (CECD), coefficient of variation of cell size (CV), central corneal thickness (CCT), hexagonality. Results: Overall, mean preoperative CECD was 2538.21+/-259.98 mm2, postoperatively at 1 month and 3 month it was significantly reduced to 2377.11+/-270.36 mm2 and 2340.56+/-272.39 mm2 respectively. (p <0.05). Overall, mean preoperative CV was 31+/-5.93%, postoperatively at 1 month and 3 month it was non-significantly increased to 33.19+/-6.02% and 34.30+/-5.97% respectively. (p>0.05). Overall, mean preoperative hexagonality was 53.63+/-4.47%, postoperatively at 1 month and 3 month it was non significantly reduced to 51.54+/-4.50% and 50.41+/-4.49% respectively (p>0.05). Overall, mean preoperative CCT was 514.41+/-13.786um, postoperatively at 1 month and 3 month it was significantly increased to 523.58+/-14.99um and 520.69+/-14.80 um respectively. (p<0.05). Conclusion: Mitomycin-C application in trabeculectomy cause significant corneal endothelial loss. Most of the damage occurs intraoperatively, or in the early postoperative period.